#Body goals or #Bopo? Exposure to pregnancy and post-partum related social media images: Effects on the body image and mood of women in the peri-pregnancy period. (September 2022) - Becker, Elizah; Rodgers, Rachel F.; Zimmerman, Emily
Abstract: Women who are pregnant or have recently given birth use social media where they may encounter content promoting appearance ideals or offering more realistic representations of the body during this unique period. To date, little is known regarding the ways in which different social media content may impact the body image and mood of women who are pregnant or postpartum. A sample of 261 participants aged 21–44, mean (SD) age = 31.79 (4.402), were randomly allocated online to view either thin-and-toned ideal or body positive social media content specific to the pregnancy and postpartum period, or a neutral travel condition. Findings revealed that exposure to the body positive images had positive effects on body image relative to the thin-and-toned ideal condition, as well as leading to increases in some indices of positive body image, while the thin-ideal images were harmful. Partial support emerged for the protective roles of body appreciation and low social media-related rumination among women exposed to the thin-and-toned ideal images. Social media content may be harmful or helpful to the body image and mood of pregnant and postpartum women, which is important given the documented relationships between maternal body image, mood, and maternal and infant outcomes. Highlights: Body positive pregnancy /postpartum social media images were associated with better body image and mood than idealized ones. Idealized images were harmful while body positive images were helpful for body image. High body appreciation and low social media rumination were somewhat protective against idealized images.